A study to evaluate the continuity of rehabilitation at home by stroke patients attending physiotherapy from the physiotherapy outpatient department at the University Teaching Hospital, UTH - Phiri, Theressa (Lusaka: University of Zambia , School of Medicine, 2014)
Physiotherapists are integral to the rehabilitation of patients that have a stroke and Home Exercise Program (HEP) prescription is a routine part of physiotherapy care. The overall goal of HEP is to gain functional independence which is accomplished with skilled rehabilitation intervention and training. The objective of this study was to evaluate the continuity of rehabilitation at home by stroke patients attending physiotherapy from the physiotherapy out patient department at UTH.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Physiotherapy.
Includes bibliographical references.
Keywords: Cerebrovascular disease--Patients--Hospital care